2020
DOI: 10.1016/j.ajoc.2020.100865
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Sporotrichosis

Abstract: Purpose To present 10 cases of Parinaud oculoglandular syndrome caused by sporotrichosis. Observations We report 10 cases of Parinaud oculoglandular syndrome after contact with domestic cats diagnosed with sporotrichosis. They all showed ocular hyperemia associated with unilateral tarsal conjunctival granulomas. After histopathological study and culture of the scrapings and conjunctival secretions, six patients were positive for Sporothrix schenkii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In this study, we identified individuals with a broad spectrum of clinical presentation, highlighting from this study the high prevalence of individuals with ocular CTS (13%). Ocular forms may occur due to contact with secretions of sick felines in the conjunctiva, demonstrating that zoonotic transmission has altered the observed profile of clinical manifestations 8,27–29 . We observed high sensitivity (92%) for the diagnosis of ocular CTS using the Anti‐Sporo LFA.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we identified individuals with a broad spectrum of clinical presentation, highlighting from this study the high prevalence of individuals with ocular CTS (13%). Ocular forms may occur due to contact with secretions of sick felines in the conjunctiva, demonstrating that zoonotic transmission has altered the observed profile of clinical manifestations 8,27–29 . We observed high sensitivity (92%) for the diagnosis of ocular CTS using the Anti‐Sporo LFA.…”
Section: Discussionmentioning
confidence: 74%
“…Twenty-one studies (case reports and case series) reported ocular sporotrichosis with involvement of the conjunctiva, representing a total of 56 patients, with a mean age of 33.33 ± 21.81 years (range 3-80 years) (Table 3) [34,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Most cases have been reported in Brazil (44 cases) and Malaysia (8 cases).…”
Section: Conjunctival Sporotrichosismentioning
confidence: 99%
“…The left eye was more commonly affected than the right one (15 vs. 12 cases, respectively), although in 29 cases, the affected eye was not specified. S. schenckii was isolated in 25% of the cases (14 patients) [39][40][41]44,47,[50][51][52][53] followed by S. brasiliensis (5.3%, 3 cases) [26,45]; isolation was not achieved in 4 patients (7.4%) [3,4,7,11], and in 35 (62.5%), the species involved was not determined [12,34,37,38,43,49]. Previous trauma related to conjunctival implantation was not reported in any patient, although contact with cats was reported in 50 patients (89.3%) (Table 3) [26,34,37,38,40,41,[43][44][45][46][47][48][49][50][51][52][53].…”
Section: Conjunctival Sporotrichosismentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular fungal infections have been reported to be caused by more than 56 genera. Among these, the most commonly involved are Candida and Aspergillus ; other unicellular and filamentous fungi such as Fusarium , Penicillium, Paecilomyces , Acremonium , Exophiala , Pseudallescheria , Scytalidium , Sporothrix , and Cryptococcus ; and dimorphic fungi [ 12 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%